Beyond the Pen: Creative Writing Innovation via Canva for Junior High School Students - Chaoro Lutfi Amalia; Irra Wahidiyati (Journal of ELT, Linguistics, and Literature, 2026)
This study examines the implementation of the Canva application as a medium for teaching writing to ninth-grade students at SMP N 1 Kebasen, Banyumas. It explores students' responses to its use. This study uses a qualitative descriptive research design. Data were collected through classroom observation and unstructured interviews with English teachers and students. The results show that Canva was used across several stages of the writing process: pre-writing, drafting, revision, editing, and publishing. However, several challenges were identified, including limited internet connectivity, generic templates, insufficient time, and technical glitches. These challenges were overcome through group work, peer assistance, and teacher guidance. In conclusion, the Canva application is a learning medium used by students and teachers at the school.